CAPITA - Treasury's microsimulation model of personal income tax and transfers - Martin Stevenson; Daniel Ledda; Virginia Pineda; Matthew Smith; Susie Kluth (The Australian Government, The Treasury, 2017)
Distributional analysis captures the wide range of policy outcomes and the diverse effects of policy changes across the population. Static microsimulation models are a commonly used tool for producing distributional analysis. Treasury has developed the CAPITA (Comparative Analysis of Personal Income Tax and Transfers in Australia) model, a general-purpose, static microsimulation model, which is used to analyse the combined effect of changes to personal income tax and transfer policy on families with different income levels, family structures and living arrangements. Treasury is releasing this model to the public to encourage rigorous, evidence-based contributions to public policy analysis in Australia. Treasury encourages users of the model to contribute and share their improvements to continue to develop and improve the model into the future.
Keywords: 330; CAPITA; static microsimulation; tax-transfer; distributional analysis